Advanced Solubility Science: Mixed Hydrotropy - Mirzapure, Isha A. (Asian Journal of Pharmaceutics (AJP), 2024)
Although the majority of the hypotheses proposed to comprehend the mechanism of hydrotropic agents have not supported the solubility enhancement mechanism, we have elaborated on a few of them in this review. In addition, the articles emphasize the factors that affect improving solubilizing capacity. Due to their special properties, hydrotropes are frequently utilized in the solubilization of drugs, as removal go-betweens for different phytoconstituents, as separation agents for pharmaceutical analysis, and for boosting the amount and harvest of biochemical reactions. Due to this, hydrotropic solutions are highly sought after in industry. Mixed hydrotropy, on the other hand, is mostly used to increase solubility, extract phytoconstituents, and discrete materials using more than one hydrotropic agent. This review paper emphasizes the applications as well. It is necessary to screen a large number of hydrotropic candidates to find the best hydrotropic agent for a poorly soluble medication. However, once the right hydrotropic agent for a medicine is found, it is simple to increase its solubility significantly. Meanwhile, the state fixes non-call for the chemical alteration of the medication, the usage of carbon-based thinners, or the creation of suspension schemes, the hydrotropic method is the prospective strategy with the most potential for poorly soluble pharmaceuticals. The main goal of this study was to increase the oral bioavailability of furosemide by improving its solubility utilizing hydrotropes and their combinations.